The prevention of neural tube defects by folic acid supplementation - H. W. Hitzeroth (AOSIS, 1993)
Neural tube defects, in particular spina bifida and anencephaly, are serious and relatively common congenital abnormalities worldwide. They also occur in South Africa and affect all population groups to varying degrees. The overall incidence in South Africa is approximately 1-2 per 1000 newborns. Higher incidences, up to 6 per 1000 newborns have been recorded in certain parts, especially in some rural areas of the country. In total as many as 1500 newborns could be affected by a neural tube defect each year. The precise aetiology of neural tube defects is still unknown.